2003
DOI: 10.1097/00061198-200304000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Glaucoma and Its Relationship with Visual Function

Abstract: Perceived visual disability relating to certain tasks (particularly involving dark adaptation and disability glare, activities demanding functional peripheral vision such us tripping over and bumping into objects and outdoor mobility tasks) was significantly associated with the severity of binocular visual field loss. As a result, a new glaucoma-specific questionnaire scale with good performance characteristics is presented in this study. The difficulties encountered by patients in everyday life (as measured w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
333
6
17

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(394 citation statements)
references
References 33 publications
21
333
6
17
Order By: Relevance
“…Patients self-report difficultly with glare and moving between environments where lighting changes. 59 We have also shown that patients with advanced visual field loss have difficulty with searching for everyday objects and face recognition. 60,61 These studies took advantage of experiments that also tracked subjects' gaze as they carried out the tasks.…”
Section: Aspects Of Visual Disability In Glaucomamentioning
confidence: 82%
“…Patients self-report difficultly with glare and moving between environments where lighting changes. 59 We have also shown that patients with advanced visual field loss have difficulty with searching for everyday objects and face recognition. 60,61 These studies took advantage of experiments that also tracked subjects' gaze as they carried out the tasks.…”
Section: Aspects Of Visual Disability In Glaucomamentioning
confidence: 82%
“…QoL is a multi-dimensional concept, yet the GQL-15 only contains items representing visual activities, which is only one dimension of QoL. 27,28 The same is true for the GSI, pretending to measure the impact of glaucoma symptoms on QoL, yet mostly containing items related to visual activities as well. 26 …”
Section: Pro's Addressing Functional Status Related To Visionmentioning
confidence: 99%
“…Overall, the tools for assessing functional status demonstrated poor quality both in view of their development as well as for their validation process. Yet, further adaptation and testing could improve instruments with potential, such as the GQL-15, IMQ and the GSI [24][25][26][27][28] Within the QoL-measures, both the Glau-QoL and VisQoL had an extensive and theory based development process, but were generated and validated according to classical techniques. [43][44][45] Applying additional Rasch-analysis could strengthen their content and validity.…”
Section: Eyementioning
confidence: 99%
“…Accordingly, several validated surveys have been developed over the past several years that evaluate the impact of glaucoma on a patient's activities of daily living and vision. [1][2][3][4][5][6][7][8][9] Further, several years ago Laibovitz et al 10 validated the Comparison of Ophthalmic Medications for Quality of Life questionnaire (COMQoL), which was designed to compare specifically the tolerability of ophthalmic medications and to evaluate the effect of ocular hypotensive therapy on side effects, routine living activities, quality of life, compliance, and patient satisfaction with medication. The data were used to show an increased preference for dorzolamide compared to pilocarpine due to reasons of side effects and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%